The Vibrio cholerae O139 serogroup antigen includes an O-antigen capsule and lipopolysaccharide virulence determinants. - Waldor, M K (1994)
Vibrio cholerae serogroup O139 emerged on the Indian subcontinent in October 1992 to become the first non-O1 V. cholerae serogroup documented to cause epidemic cholera. Although related to V. cholerae El Tor O1 strains, O139 strains have unique surface structures that include a capsular surface layer and lipopolysaccharide (LPS). Immunoblot analysis of either whole-cell lysates or LPS preparations revealed three electrophoretic forms of the O139 antigen: two slowly migrating forms and one rapidly migrating form that appeared identical to O139 LPS. All three forms of the antigen shared an epitope defined by an O139-specific monoclonal antibody. A serum-sensitive nonencapsulated mutant was isolated that lacks only the slow migrating forms. The slow migrating forms did not stain with silver whereas the rapidly migrating form did, suggesting that the former might constitute highly polymerized O-antigen side-chain molecules that were not covalently bound to core polysaccharide and lipid A (an "O-antigen capsule"). A single transposon insertion resulted in the loss of immunoreactivity of both the LPS and the O-antigen capsule, implying that there are genes common to the biosynthesis of both these macromolecules. The O139 LPS and O-antigen capsule were both important for colonization of the small intestine of the newborn mouse and for serum resistance, demonstrating that both of these forms of the O139 serogroup antigen are virulence factors.